2019
DOI: 10.1515/chem-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

Studies On Compatibilization Of Recycled Polyethylene/Thermoplastic Starch Blends By Using Different Compatibilizer

Abstract: In this study, the aim was to examine the effects of three different compatibilizers on the recycled polyethylene/ thermoplastic starch (r-LDPE/TPS) blends which are used in producing garbage bags. Polyethylene-Grafted-Maleic Anhydride (PEgMAH), maleic-anhydride modified ethylene propylene rubber (EPMgMAH) and ethylene maleic anhydride copolymer (PEMAH) were selected as the compatibilizers. r-LDPE/TPS blends with or without compatibilizer were prepared by using a twin screw extruder and characterized by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…In the literature, several studies are examining the properties of PE/TPS blends. [13,17] However, since these materials have a relatively high interfacial tension, they show poor mechanical properties due to the poor phase compatibility between nonpolar PE and the high polarity of TPS. [10,13,17] Besides, deterioration in transparency, tensile elongation and strength, tear-strength, and gas barrier properties of PE/TPS blends have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, several studies are examining the properties of PE/TPS blends. [13,17] However, since these materials have a relatively high interfacial tension, they show poor mechanical properties due to the poor phase compatibility between nonpolar PE and the high polarity of TPS. [10,13,17] Besides, deterioration in transparency, tensile elongation and strength, tear-strength, and gas barrier properties of PE/TPS blends have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[13,17] However, since these materials have a relatively high interfacial tension, they show poor mechanical properties due to the poor phase compatibility between nonpolar PE and the high polarity of TPS. [10,13,17] Besides, deterioration in transparency, tensile elongation and strength, tear-strength, and gas barrier properties of PE/TPS blends have been reported. [17][18] To overcome the incompatibility problem between the PE and TPS, the addition of nanofillers and various compatibilizer such as polyethylene-grafted maleic anhydride (PE-g-MA) has been suggested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical incompatibility between hydrophilic TPS and the hydrophobic PP, which worsens the mechanical properties. To overcome this issue, some polyolefin grafted with maleic anhydride (MA) is widely used [22][23][24]. However, MA is expensive, difficult to manufacture and like petroleum-based polymers, non-biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…12 Another method to make suitable polymer blends is to mix reactively in situ or to use a compatibilizer that contains maleic anhydride (MAH). 13,14 The anhydride group can graft other polymers at the melt temperature due to its high reactivity in subsequent processes. Bikiaris et al, found in their study conducted in 1998 that polyethylene-g-maleic anhydride co-polymers (PE-g-MAH) was the most effective compatibilizers in LDPE/ plasticized starch (PLST) blends.…”
mentioning
confidence: 99%